2013
DOI: 10.1371/journal.pone.0069070
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Population Structure and Reproductive Mode of the Termite Reticulitermes chinensis Snyder

Abstract: The subterranean termite Reticulitermes chinensis Snyder is an important pest of trees and buildings in China. Here, we characterized genetic structure and reproductive modes of R. chinensis from China for the first time. A total of 1,875 workers from 75 collection sites in Huanggang, Changsha and Chongqing cities were genotyped at eight microsatellite loci. Analysis of genetic clusters showed two subpopulations in Chongqing city. The Huanggang population showed a uniform genetic pattern and was separated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…A color marker was added to 5 -primers and all primers synthesized by Invitrogen Trading (Shanghai, China) Co., Ltd. GeneMapper v4.0 (Applied Biosystems, Foster City, CA, USA) and Peak Scanner v1.0 (Applied Biosystems, Foster City, CA, USA) were used for analysis. Both the R. flaviceps and R. chinensis are non-parthenogenetic species [15]. The offspring produced by sexual reproduction were diploid.…”
Section: Genotyping Analysesmentioning
confidence: 99%
“…A color marker was added to 5 -primers and all primers synthesized by Invitrogen Trading (Shanghai, China) Co., Ltd. GeneMapper v4.0 (Applied Biosystems, Foster City, CA, USA) and Peak Scanner v1.0 (Applied Biosystems, Foster City, CA, USA) were used for analysis. Both the R. flaviceps and R. chinensis are non-parthenogenetic species [15]. The offspring produced by sexual reproduction were diploid.…”
Section: Genotyping Analysesmentioning
confidence: 99%
“…In China, Reticulitermes chinensis Snyder, an important pest of trees and buildings from the genus Reticulitermes were also genotyped at eight microsatellite loci. Analysis of genetic clusters showed that the two subpopulations in Chongqing city were headed by outbred unrelated pairs (Huang et al, 2013). Their study also showed that dispersal by primary reproductives was relatively limited due to the short range mating flight or due to the frequent colony reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…The subterranean termites Reticulitermes chinensis Snyder are widely distributed throughout China, causing serious damage to structures and forests and bringing huge economic losses 27 28 . In this study, we used R. chinensis as the test organism to determine whether termites employ active immunization to defend against the entomopathogenic fungus Metarhizium anisopliae by employing multi-level methods, combing iTRAQ LC-MS/MS technology with MRM assays to find immune proteins involved in the active immunization of R. chinensis .…”
mentioning
confidence: 99%